THE INFLUENCE OF GUIDED INQUIRY LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES IN VIRUS TOPIC - M.Pd, Samsuar; Farissi Hamama, Syarifah (Jurnal Penelitian Progresif, 2025)
The aim of this study is to determine the effect of the guided inquiry learning model on students' learning outcomes in the topic of viruses for Class X at SMA N 1 Baitussalam. This research employs a quasi-experimental design with a pre-test post-test control group design using a quantitative approach. The sampling technique used is purposive sampling, where Class X-1, consisting of 28 students, serves as the experimental class, while Class X-2, consisting of 27 students, serves as the control class. The research instrument consists of 20 multiple-choice test questions, and data analysis is conducted using the percentage formula to calculate students' learning outcomes, the N-gain test to measure the improvement in students' learning outcomes, and the Independent Sample T-test using SPSS 27 to test the hypothesis. The data analysis results show that: (1) the average learning outcome of the experimental class is higher at 86.61 compared to the control class, which is 73.33; (2) the N-gain value for the control class is 0.44, while for the experimental class, it is 0.60, indicating that the improvement in learning outcomes in both classes falls into the medium category; (3) the hypothesis testing using the Independent Sample T-Test resulted in a significance value (sig. 2-tailed) of 0.00 < 0.05, leading to the rejection of H0 and acceptance of Hα. This finding indicates that the guided inquiry learning model has a significant effect on students' learning outcomes in the topics of viruses for Class X at SMA N 1 Baitussalam.